Information Security Governance Simplified : From the Boardroom to the Keyboard - Todd Fitzgerald (CRC Press, 2012)
Security practitioners must be able to build a cost-effective security program while at the same time meet the requirements of government regulations. This book lays out these regulations in simple terms and explains how to use the control frameworks to build an effective information security program and governance structure. It discusses how organizations can best ensure that the information is protected and examines all positions from the board of directors to the end user, delineating the role each plays in protecting the security of the organization.